2019
DOI: 10.22438/jeb/39/6/mrn-700
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and drought stress on barley and wheat cultivars planted in Turkey

Abstract: The study was conducted to investigate the salinity and drought susceptibilities of barley and wheat varieties cultivated in Turkey by phenotypic assays and to evaluate the association of WRKY19 and WRKY52 transcription factors with salinity and drought stresses by gene expression assays. Salinity tests of treatment different concentration of (0, 0.5, 1 and 2%) NaCl were managed with 13 barley and 22 wheat varieties germinated for 10 days. According to findings obtained from phenotypic investigations, two rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In this study, we showed that there was great variation in EC capacity of barley and wheat lines. Similarly, in comparison to previous studies relatively drought resistant lines, which could be used in further studies, were detected (Suprunova et al, 2004;Yörük et al, 2018).…”
Section: Microsatellite Pcr Genotyping Analysissupporting
confidence: 58%
See 1 more Smart Citation
“…In this study, we showed that there was great variation in EC capacity of barley and wheat lines. Similarly, in comparison to previous studies relatively drought resistant lines, which could be used in further studies, were detected (Suprunova et al, 2004;Yörük et al, 2018).…”
Section: Microsatellite Pcr Genotyping Analysissupporting
confidence: 58%
“…Barley and wheat have a great significance in economies of many countries including Turkey. Several investigations have been conducted on drought and salinity response of barley and wheat cultivars planted in Turkey (Gürel et al, 2016;Yörük et al, 2018;Tufan et al, 2020). However, limited number of barley and wheat lines were investigated in terms of physiological and genetic differences of lines planted/cultivated in Turkey.…”
Section: Microsatellite Pcr Genotyping Analysismentioning
confidence: 99%
“…WRKY, bZIP, MYB, bHLH, AP2/ERF, NAC and homeodomain TFs have been shown to participate in the regulation of stress responses [6,7,8,9,10]. WRKYs have vital roles in plant defense against abiotic and biotic stresses as well as involved in many developmental processes such as seed development, dormancy, leaf senescence, and trichome development and some signal transduction processes mediated by plant growth regulators [11,12,13]. WRKYs have conserved 60 amino acid regions comprising of the highly conserved WRKYGQK peptide sequence and a zinc finger like motif.…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings, no germination was observed in 2.0 % NaCl treated experiment sets. Significantly decreased to 2.0 % NaCl treatment in wheat and barley cultivars was an expected result since NaCl causes strong salt stress for many plant species (Badridze et al, 2009;Almodares et al, 2014;Jain et al, 2016;Yörük et al, 2018). Thus, further transcript analysis was carried with 0 % and 1.0 % NaCl treated sets.…”
Section: Resultsmentioning
confidence: 88%